Implementation of Zhang's Camera Calibration Algorithm on a Single Camera for Accurate Pose Estimation Using ArUco Markers - Herdiansyah, Junardo; Putra, Febi Ariefka Septian; Septiyanto, Dwi (Peneliti Teknologi Teknik Indonesia, 2024)
Pose estimation using ArUco markers is a method to estimate the position of ArUco markers relative to the camera lens. Accurate pose estimation is crucial for autonomous systems to navigate robots effectively. This study aims to achieve an ArUco Marker pose estimation accuracy of at least 95% using a single camera. The method employed to obtain accurate ArUco pose estimation results is by calibrating the camera with the Zhang camera calibration algorithm. This calibration is necessary to obtain the camera matrix and distortion coefficients, thereby enhancing the accuracy of the pose estimation results. The results of this study include achieving a cumulative calibration error of 0.0180 pixels and pose estimation errors at a distance of 50 cm between the marker and the camera lens. The accuracy on the X-axis was 100%, the Y-axis was 100%, and the Z-axis was 99.823%. At a distance of 70 cm, the pose estimation accuracy on the X-axis was 99.349%, on the Y-axis was 99.462%, and on the Z-axis was 99.066%. At a distance of 100 cm, the pose estimation accuracy on the X-axis was 96.349%, on the Y-axis was 97.641%, and on the Z-axis was 99.344%.